Antunin Family Gradojević – Bratutović from Dubrovnik, Originally from Trebinje - Pekić, Radmilo B. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This work shows the historical developement of one of many city families in Dubrovnik which, according to Dubrovnik genealogies, during the middle ages arrived from Serbian countries. The focus is on the family Gradojević – Bratutović, whose founder moved from Trebinje, from Dukats of St. Sava to Dubrovnik in the thirties of the 15th century and soon became full-fledged citizen of Dubrovnik. The founder of the family, Bratut Gradojević was a clothier, he produced and sold clothes. He cooperated with other traders and his business was creditworthy. As a prominent merchant, he gained fortune and became a member of prominent Antunin association, which gathered the richest class of citizenry from Dubrovnik. His descendants proceeded with the same practice and thus enlarged family capital. Apart from Dubrovnik, family members also owned land in Primorje in the settlement of Visočani. They had possession in Konavle where they grew various cereals. Family Gradojević – Bratutović lasted over 200 years in Dubrovnik. This family derived a prominent dragoman Vicko Bratutović, an excellent expert of oriental languages, who worked as an interpreter for emperor Ferdinand III. Later he worked on the Spanish court where his life ended.